2000
DOI: 10.1039/a908976d
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of styrene-7,8-oxide and other oxidation products of styrene in air

Abstract: Styrene-7,8-oxide (SO) is generated at low concentrations from the oxidation of styrene during the processing of reinforced plastics. Since exposure to SO has important health implications, we developed air sampling and analytical methods to measure low levels of airborne SO in the presence of styrene and its other oxidation products, namely phenylacetaldehyde (PAA) and acetophenone (AP). Both active and passive air monitors were used. The active sampling method, which employed adsorption on Tenax, was suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…As expected this subject was also the one with the highest level of urinary biomarkers (see Figure 2). StyOX exposure in these workers was about three orders of magnitude lower than that of Sty, and in good agreement with previously published data (Pfäffli & Säämänen 1993, Nylander-French et al 1999, Tornero-Velez et al 2000. Moreover, we report for the first time that exposure to StyOX was measured during the production of varnishes that employed styrene as an ingredient.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected this subject was also the one with the highest level of urinary biomarkers (see Figure 2). StyOX exposure in these workers was about three orders of magnitude lower than that of Sty, and in good agreement with previously published data (Pfäffli & Säämänen 1993, Nylander-French et al 1999, Tornero-Velez et al 2000. Moreover, we report for the first time that exposure to StyOX was measured during the production of varnishes that employed styrene as an ingredient.…”
Section: Discussionsupporting
confidence: 92%
“…Occupational exposures to styrene are accompanied by co-exposures to low levels of styrene-(7,8)-oxide (StyOX), which is produced from oxidation of Sty during the production of plastics, possibly via catalysis by hydroperoxides used as initiators of the polymerization process , Nylander-French et al 1999, Tornero-Velez et al 2000. StyOX is an animal carcinogen that is classified as a probable human carcinogen (group 2A) (IARC 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of free radicals are produced during a short period of time to initiate the formation of polymers. Under such strong oxidizing conditions, styrene, the starting material for the polystyrene nanosphere, might be oxidized to styrene-7,8-oxide (SO), phenylacetaldehyde and acetophenone [32]. As indicated in Figure 5, the supernatant of 1.0 mg/mL PSNS suspension depicted a strong UV-visible absorption peak at 210 nm, a pattern similar to the characteristic peak of pure SO.…”
Section: Resultsmentioning
confidence: 92%
“…2 Although rarely mentioned, direct exposures to SO can also occur at low (mg/m 3 ) levels in styrene-using industries where SO is released into air as a byproduct of styrene oxidation. [6][7][8][9][10][11] The biological importance of SO is generally considered within the context of styrene metabolism due to the vastly greater abundance of styrene in air. However, this assumption has been questioned because, whereas metabolically derived SO is efficiently detoxified by epoxide hydrolases in the liver, inhaled SO is rapidly absorbed and distributed to the tissues where it can exert genotoxic effects.…”
mentioning
confidence: 99%
“…However, this assumption has been questioned because, whereas metabolically derived SO is efficiently detoxified by epoxide hydrolases in the liver, inhaled SO is rapidly absorbed and distributed to the tissues where it can exert genotoxic effects. 6 8 12 Different factors have been linked to increased levels of styrene exposure in the FRP industry. In a review of industrial hygiene surveys, Lemasters et al 13 observed significant differences in airborne styrene levels due to the type of product (highest in the boat and truck manufacturing groups) and the type of process (open moulds higher than press moulds).…”
mentioning
confidence: 99%